2019
DOI: 10.4236/ojcd.2019.94011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the TbgI<sub>2</sub> and TbgI<sub>17</sub> Tandem Repeat Antigens as Potential Antigens for the Diagnosis of <i>Trypanosoma brucei rhodesiense</i>

Abstract: Human African trypanosomiasis (HAT) affects up to half a million people every year in sub-Saharan Africa. Interruption of transmission of the disease by early diagnosis and treatment is core to the control and eventual elimination of HAT. The routine diagnostic method for HAT is light microscopy of blood samples. The present study sought to evaluate the potential of TbgI 2 and TbgI 17 tandem repeat antigens as candidates for the diagnosis of Trypanosoma brucei rhodesiense. The expressed proteins were purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
1
1
Order By: Relevance
“…Several studies have shown that the main limitation of single protein based assays is often lack of sensitivity [19,22,25,26]. As expected, this pattern of response is equally present for the two tested proteins.…”
Section: Diagnostic Potential Of Tblysopla and Tbgk As A Mixture And Combined With C25supporting
confidence: 69%
“…Several studies have shown that the main limitation of single protein based assays is often lack of sensitivity [19,22,25,26]. As expected, this pattern of response is equally present for the two tested proteins.…”
Section: Diagnostic Potential Of Tblysopla and Tbgk As A Mixture And Combined With C25supporting
confidence: 69%
“…The concentrations of Tbg I2 and Tbg I17 expressed proteins were 0.345 and 0.221 mg/mL, respectively presented in the Table 1. The study conducted by Irumva et al, 2019 reported a concentration for Tbg I2 and Tbg I17 expressed proteins of 1.299 mg/mL and 0.517 mg/mL, respectively [13]. These differences can be related to the short time given for the culture to grow in our study, whereas a long time was given for the culture to grow in Irumva et al's 2019 study.…”
Section: Discussioncontrasting
confidence: 54%
“…Unlike other immunoassays such as ELISA and immunoblot, immunoassays using flow cytometers apply lasers that recognize only the soluble particles marked and of pre-established size. Recent studies have demonstrated its potential use in new applications [22,23]. This methodology presents a minimum interference of unmarked particles, thus allowing reduction of the washing steps, handling and testing time [24,25].…”
Section: Magnetic Bead Assay Specifically Detect Hcv Positive Samplesmentioning
confidence: 99%